I seem to run into another problem in my homework. (I could see it coming If: f (x) = 3(x+1)^2 (the last 2 means square) g (x) = (2/x) - 1 what is (f *g)(x) (multiplication) thank you
Follow Math Help Forum on Facebook and Google+
Hello, Originally Posted by zdenka I seem to run into another problem in my homework. (I could see it coming If: f (x) = 3(x+1)^2 (the last 2 means square) g (x) = (2/x) - 1 what is (f *g)(x) (multiplication) thank you If I'm not misreading : $\displaystyle (f*g)(x)=f(x)*g(x)=3(x+1)^2 * (\frac 2x-1)=3(x+1)^2 * \frac{2-x}{x}$ It cannot be much simplified.. It depends on how you want it to be
You read it correctly. thank you. I just never know when to stop the simplification and then I end up with a nonsense equation. I have one more combining question. I will post it in a bit.
View Tag Cloud